An isochore map of human chromosomes - Costantini, Maria (Cold Spring Harbor Laboratory Press, 2006)
Isochores are large DNA segments (≫300 kb on average) that are characterized by an internal variation in GC well below the full variation seen in the mammalian genome. Precisely defining in terms of size and composition as well as mapping the isochores on human chromosomes have, however, remained largely unsolved problems. Here we used a very simple approach to segment the human chromosomes de novo, based on assessments of GC and its variation within and between adjacent regions. We obtain a complete coverage of the human genome (neglecting the remaining gaps) by ∼3200 isochores, which may be visualized as the ultimate chromosomal bands. Isochores visibly belong to five families characterized by different GC levels, as expected from previous investigations. Since we previously showed that isochores are tightly linked to basic biological properties such as gene density, replication timing, and recombination, the new level of detail provided by the isochore map will help the understanding of genome structure, function, and evolution.